The reliability and validity of the Japanese version of the Children's ChronoType Questionnaire (CCTQ) in preschool children. (November 2014) - Ishihara, Kaneyoshi; Doi, Yuriko; Uchiyama, Makoto
<x xml:space="preserve">Abstract</x> We aimed to examine the reliability and validity of the Japanese version of the Children's ChronoType Questionnaire (CCTQ) in preschool children. The CCTQ consists of 16 items on sleep–wake parameters for scheduled and free days, a 10-item of the Morningness/Eveningness Scale (CCTQ-M/E), and a single item on chronotype. Out of 502 children aged 3–6 years living in Okayama Prefecture, we evaluated 346 (188 boys and 158 girls) between May and June 2012. Their parents filled out the questionnaires two times at an interval of two weeks. Cronbach's α of the CCTQ-M/E was 0.77. For test–retest reliability, Pearson's correlation coefficient of the CCTQ-M/E between the two observations was 0.898 (p < 0.001). Kruskal–Wallis test with post-hoc tests was used to compare sleep–wake parameters measured with the CCTQ among the three groups of children, morning (M)-type, neither (N)-type and evening (E)-type, who were classified according to the CCTQ-M/E score. Sleep–wake parameters in timing were significantly different among the children with M-type, N-type and E-type (p < 0.001). Post-hoc pairwise comparisons revealed that sleep–wake parameters in timing were significantly delayed from the M-type to the N-type children (p < 0.001), from the M-type to the E-type children (p < 0.001), and from the N-type to the E-type children (p < 0.001), except that wake-up time and get-up time were not significantly different between the children with N-type and E-type on scheduled days when their start time was regularly fixed. Out of these 346 children, we evaluated 72 (35 boys and 37 girls) to see the correlations between subjectively and objectively measured sleep–wake parameters from June to October 2012. Spearman's correlation coefficients between sleep–wake parameters measured with the CCTQ and an actigraph were 0.512–0.836 on scheduled days (p < 0.001) and 0.380–0.786 on free days (p < 0.001). Based on these findings we conclude that the Japanese version of the CCTQ is a reliable and valid measure for assessing chronotypes in preschool children.